Pengaruh Pemberian Edukasi Seksual Terhadap Pengetahuan Seksual Sebagai Bentuk Pencegahan Pelecehan Seksual Pada Siswa Sekolah Dasar - ’Akli, Zul; M, Muhibuddin; Abidin, Zainal; Kalsum, Ummi (Nanggroe: Jurnal Pengabdian Cendikia, 2023)
Education is a conscious and planned effort1 to create learning conditions and learning activities so that participants actively develop their abilities in having religious abilities, self-control, personality, intelligence, noble morals, and knowledge needed by students, society, nation and state (Law No. 20 of 2003 concerning the National Education System). Children are the most important and valuable asset for both parents. Many parents have high hopes for their children to become successful people in the future. However, in recent years there has been a lot of news about sexual abuse of children which has made many parents worried. Sexual abuse of children can occur outside the home, at home and even at school, the perpetrators can be carried out by friends, parents, siblings or teachers. Such as teasing, showing genitals, kissing, hugging and so on, this community service is carried out using socialization methods, lectures, discussions, questions and answers and legal education regarding the importance of the influence of providing sexual education on sexual knowledge as a form of preventing sexual harassment in elementary school students. in Lamkuta Village, Kuta Makmur District, North Aceh Regency. The result of this counseling is that students know how to protect themselves from perpetrators of sexual harassment around them. The children enthusiastically participated in Sexual Education on Sexual Knowledge as a Form of Preventing Sexual Harassment in Elementary School Students.